PENERAPAN METODE BRAINSTORMING DALAM PEMBELAJARAN TEKS BERITA PADA SISWA KELAS VIII MTS. AL MUFTI - Jajang Suparman; Oseu Liana; Heri Isnaini (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2019)
Researchers find problems in learning news text students are difficult to express ideas and and students do not understand the interesting grammar and how to identify news texts. Researchers use brainstorming models to motivate students and develop ideas and imagination in writing news texts. This study aims to determine the differences in the ability and implementation of student learning that is applied to the treatment of discovery learning models in the control class and students who are applied to the treatment model of brainstorming in the experimental class. In this research the method used is Quasi Experimental Design that is used is pretest-posttest Control Group Design. The object of this research sample are 30 students of VII-A class, and 30 students of VII-B class. When students are given treatment by applying the brainstorming model, the value obtained is very good, it can be seen from the posttest results that the average student gets a score of 81.96, compared to when students are treated (treatment) using the average discovery learning model. students only scored 76.70.